Nasal cells as a bronchial cell surrogate for pre-clinical assessment of drug response in cystic fibrosis - Barillaro, Malina; Avolio, Julie; Balachandran, Sharaniyaa; Bartlett, Claire; Ip, Wan; Ouyang, Hong; Duan, Wenming; Zabner, Joseph; Keshavjee, Shaf; Bear, Christine; Moraes, Theo J.; Gonska, Tanja (Frontiers in Pharmacology, 2025)
Patient-derived airway cell cultures are used in personalized medicine strategies for people with cystic fibrosis (pwCF) to predict potential clinical response to cystic fibrosis transmembrane conductance regulator (CFTR) modulator drugs. While bronchial epithelial cells from lung explants (HBEx) are the gold standard for CFTR functional measurements, nasal epithelial cells (HNE) are a more practical tissue source resulting in widespread use for preclinical functional platforms. HNE have so far not been rigorously validated against the gold standard for this purpose. In this study, we collected nasal and bronchial cells, and lung explants from pwCF undergoing lung transplantation as well as non-CF controls. Comparative studies in non-CF cells showed that while CFTR-mediated transepithelial currents in HNE underestimated those in HBEx, the magnitude of the CFTR modulator response was similar between CF HNE, brushed HBE (HBEb), and HBEx with significant correlation between matched HNE and HBEb from 16 pwCF. These findings confirm use of HNE as surrogate of bronchial airway for preclinical drug testing with report of drug responses in relation to the tissue-specific non-CF or baseline controls rather than as absolute results. Furthermore, CF centres offering HNE-based drug testing utilize different techniques, challenging the comparison of results between centres. We show how culture media, use of fresh or freeze-thawed cells as well as difference in Ussing technique impact the magnitude of measured CFTR function, which is why we suggest diligence in reporting of these factors when presenting CFTR modulator drug response results.